Trochanteric pain and total hip arthroplasty: a systematic review of the literature. Issue 4 (July 2020) - Axelrod, Daniel; Madden, Kim; Khan, Habeeb; Banfield, Laura; Winemaker, Mitchell; DeBeer, Justin; Wood, Thomas J.
Abstract : Background: Total hip arthroplasty (THA) is one of the most common surgical procedures. Although THA surgeries are typically very successful, between 3% and 17% of all patients experience trochanteric pain after surgery. There is little high-quality evidence on this disorder, especially after total hip arthroplasty. The purposes of this review were to describe the prevalence, treatments, prognosis, risk factors, and diagnostic methods available for trochanteric pain among preoperative or postoperative primary THA patients. Methods: The authors conducted a systematic review of trochanteric pain among THA patients. PUBMED, EMBASE, CINAHL, and the Cochrane Library were searched to identify relevant articles. Two reviewers systematically screened studies and extracted data independently in duplicate. This study presents descriptive statistics and pooled prevalence of trochanteric pain. Results: We included 36 studies with 7826 patients (mean age of 62 yr, 59% female). The prevalence of trochanteric pain was reported in 25 studies, with a mean prevalence of 3.8% (95% CI 3.3% to 4.4%). Methods of treatment for trochanteric pain included corticosteroid injections, bursectomy, and iliotibial (IT) band lengthening. Risk factors for trochanteric pain were inconsistently reported, but those most commonly listed were female gender and postoperative leg-length discrepancy. Conclusions: Approximately one in 25 patients who has undergone standard THA experiences postoperative trochanteric pain. With low certainty, the results of this review suggest the surgical approach may not influence incidence of trochanteric pain. The heterogeneity in both diagnostic modalities reported and in treatment options suggests that further prospective research is required to better inform treatment decisions for this common condition. Level of Evidence: Level III.